2018
DOI: 10.1186/s12870-018-1420-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic and biochemical evidence for adaptive evolution of leaf abaxial epicuticular wax crystals in the genus Lithocarpus (Fagaceae)

Abstract: BackgroundLeaf epicuticular wax is an important functional trait for physiological regulation and pathogen defense. This study tests how selective pressure may have forced the trait of leaf abaxial epicuticular wax crystals (LAEWC) and whether the presence/absence of LAEWC is associated with other ecophysiological traits. Scanning Electron Microscopy was conducted to check for LAEWC in different Lithocarpus species. Four wax biosynthesis related genes, including two wax backbone genes ECERIFERUM 1 (CER1) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…The up-regulation and expression was markedly higher in ROC22 compared to Badila ( Figure 8 B). ECERIFERUM1 is the skeleton gene of wax biosynthesis [ 24 ]. We found 13 ECERIFERUM1 genes that were up-regulated in sugarcane exposed to drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…The up-regulation and expression was markedly higher in ROC22 compared to Badila ( Figure 8 B). ECERIFERUM1 is the skeleton gene of wax biosynthesis [ 24 ]. We found 13 ECERIFERUM1 genes that were up-regulated in sugarcane exposed to drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…On a biome‐integrated scale, the n‐ alkane patterns in tropical South American and African savannas and shrublands show remarkable consistency despite the different evolutionary origin of the savannas on these continents (Edwards et al., 2010). This may be the result of convergent adaptation of leaf‐wax n‐ alkane traits of the dominant grass and shrubland species to environmental factors (Yang et al., 2018), or represent traits deeply rooted in plant phylogeny. Given that there are additional factors such as altitude and climate variables that affect n ‐alkane distributions (Bush & McInerney, 2015; Feakins et al., 2016), we emphasize that the chemotaxonomic significance of our sampling is limited to the study region.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of star-shaped crystal idioblasts was observed in the stem sections ( Figure 2 d). It may be suggested that the presence of crystals in the stem sections of D. villosa may serve as a taxonomical informative character [ 23 ] and, perhaps a mechanism by the plant to remove excess electrolyte storage within the plant [ 24 ]. The mechanism allows identifying the crystal idioblasts which vary in shape and size.…”
Section: Discussionmentioning
confidence: 99%